Climatology of the lightning in the northern of Benin Republic - KOUGBEAGBEDE, Hilaire; WAIDI, M. Onah; ADECHINAN, A. Joseph; GUEDJE, KOSSI FRANÇOIS; HOUNGNINOU, BODOUN ETIENNE (My University, 2020)
Lightning climatology based on World Wide Lightning Location Network (WWLLN) data is examined in detail for the first time in Benin. 1160196 flashes are reconstructed from the return arcs located by WWLLN for the entire study period, 2005 to 2017. The detection efficiency of the WWLLN network is determined from Lightning Imaging Sensor (LIS) data covering the period from 2005 to 2015. It is generally low but increases from 0.11% in 2005 to 8.09% in 2015. The proportion of single arc flashes reaches about 88% in the early years compared to about 76% in 2017, while the average multiplicity of the period is about 1.13. The results show an annual cycle with high electrical activity between April and October and low activity between November and March. The maximum monthly proportion of the period is 19.1% obtained in September. The diurnal cycle shows maximum activity around 18:00 UTC and minimum activity between 10:00 and 11:00 UTC. The maximum annual density is 13.93 fl.km -2 yr -2 and the maximum number of days when thunder rumbled at least once is 299 obtained in 2013. The electrical activity is closely related to the relief of the region. However, an anomaly is to be noted in the WWLLN data for the years 2009 and 2010 that this study was unable to elucidate.
Keywords: WWLLN; LIS; Lightning density; Detection efficiency; ! Benin.